Owad w pułapce, czyli egzystencja w nieswoim świecie. Interpretacja motywu poetyckiego - Mazan-Mazurkiewicz, Alicja (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2009)
The article deals with the problem of animal pain in contemporary Polish poetry. The author is interested in motif of trapped insect. The analysis focuses on two poems: by Janusz Szuber and by Joanna Pollakówna. The author try to explain the ideas connected with this poetical image.